Textile study courses – evaluation of student performance over one complete decade - Boris Mahltig (Communications in Development and Assembling of Textile Products)
The success of students and their performance are influenced by manifold parameters. The current study focusses especially on the correlation between study duration and the student performance. Investigated are the numbers of two textile related courses (bachelor and master) over the complete time frame of one decade. Data of more than 800 students are considered. Data evaluation is done with the final marks of the students and by using a calculated value – the student performance index PI. Especially discussed is the behavior of long-time students needing more than the double of the regular study duration. In this study only results of students are discussed which successfully finished the study course with a degree. Students leaving without a degree are not considered. For the bachelor course a correlation of their final grades with larger study duration can be determined. In contrast, for the master course nearly no influence of the study duration on the student performance is determined. A possible explanation for these different results can be discussed with the different reasons for longer study duration. For master course it is obviously the situation that the studying is combined with part-time or even full-time jobs. This combination of job and study course leads even for excellent students to prolonged study duration. With this background, for future developments a special designed part time master study course should be developed and offered for students who like the combination of a job carrier with gaining simultaneously a master degree.